Does financial information transparency and objectivity matter for stock market development? A panel regression analysis for the selected European countries - Lazarov, Darko; Lakovic, Tanja; Miteva-Kacarski, Emilija (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper investigates whether financial transparency and objectivity matter for stock market development. We test this hypothesis by using a sample of 38 selected European economies for the period 2006-2014 by applying dynamic panel regression analysis (Generalized Method of Moments). The strength of auditing and reporting standards (SARS) is used as the approximated variable for measuring the financial transparency and objectivity, while the stock market capitalization relative to GDP is a commonly used variable for stock market development. The estimated results indicate that financial information quality has a positive and significant impact on stock market development after controlling for the standard macroeconomic and financial specific stock market determinants, suggesting that financial reporting quality is one of the most important determinants of stock market development. The effects of financial reporting and auditing standards to stock market development are much more significant in the case of the non-EU countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 121-129
Keywords: financial information; stock markets development; Generalized Method of Moments; European economies; informacja finansowa; rozwój giełd; uogólniona metoda momentów; gospodarki europejskie